Haploinsufficiency of the NF1 gene is associated with protection against diabetes - Kallionpää RA; Peltonen S; Leppävirta J; Pöyhönen M; Auranen K; Järveläinen H; Peltonen J (BMJ Group, 2022)
Abstract Background The hereditary predisposition to diabetes is only partially explained by genes identified so far. Neurofibromatosis type 1 (NF1) is a rare monogenic dominant syndrome caused by aberrations of the NF1 gene. Here, we used a cohort of 1410 patients with NF1 to study the association of the NF1 gene with type 1 (T1D) and type 2 diabetes (T2D). Methods A total of 1410 patients were confirmed to fulfil the National Institutes of Health diagnostic criteria for NF1 by individually reviewing their medical records. The patients with NF1 were compared with 14 017 controls matched for age, sex and area of residence as well as 1881 non-NF1 siblings of the patients with NF1. Register-based information on purchases of antidiabetic medication and hospital encounters related to diabetes were retrieved. The Cox proportional hazards model was used to calculate the relative risk for diabetes in NF1. Results Patients with NF1 showed a lower rate of T2D when compared with a 10-fold control cohort (HR 0.27, 95% CI 0.17 to 0.43) or with their siblings without NF1 (HR 0.28, 95% CI 0.16 to 0.47). The estimates remained practically unchanged after adjusting the analyses for history of obesity and dyslipidaemias. The rate of T1D in NF1 was decreased although statistically nonsignificantly (HR 0.58, 95% CI 0.27 to 1.25). Conclusion Haploinsufficiency of the NF1 gene may protect against T2D and probably T1D. Since NF1 negatively regulates the Ras signalling pathway, the results suggest that the Ras pathway may be involved in the pathogenesis of diabetes.